Factors affecting farmers’ intention to convert to organic agricultural production – a case study in hanoi, vietnam - TUAN, PHAM VAN; TRUNG, NGUYEN ĐÌNH (The journal of contemporary issues in business and government, 2021)
In this study, the author has given different basis to build hypothesis and research models to find out the factors affecting the farmer’s intention to follow organic agriculture. Firstly, this paper focuses on studying the relationship between attitudes, subjective norms and the ability to control over the intention of converting to organic farming. Secondly, the author studies the effects of comparative behavioral advantages, risk perception, and support policies from government on organic agricultural production. The main research subjects are factors affecting farmers’ intention to produce organic agriculture. Hence, this research was conducted based on survey results among farmers. For the intention of adopting organic agriculture, the factor of comparative behavior advantage is considered as the strongest effect (β = 0.189) and the impact of other factors such as attitudes, subjective norms, the ability to control, personal standards, and the government’ support policies is negligible. In particular, the study results show that there is no statistical evidences regarding risk perception has a direct and positive relationship with farmers’ intention to produce organic agriculture among these farmers (β = 0.021, P-value> 0.05).